Acid/base properties and reactivity of square planar complexes - Dvořáčková, Olga (Jihočeská univerzita, 2022)
Complexes of platinum and other transition metals are important compounds with many applications including anticancer treatment. This thesis is based on the computational studies dealing with the properties and reactivity of square planar complexes. We showed that the central metal atom acts as a Lewis acid in standard coordination bonds but is able to interact as a Lewis base when being in contact with a Lewis acid. Substitution(s) of the nonleaving ligand(s) enabled a fine-tuning of the reactivity of Pt(II) compounds.
Acid/base properties and reactivity of square planar complexes
Keywords: platinum; Lewis acid; Lewis base; reactivity; substitution effect; trans effect